2017
DOI: 10.1038/s41598-017-09855-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of ecosystem CO2 fluxes to grazing intensities – a five-year experiment in the Hulunber meadow steppe of China

Abstract: Grazing is the primary land use in the Hulunber meadow steppe. However, the quantitative effects of grazing on ecosystem carbon dioxide (CO2) fluxes in this zone remain unclear. A controlled experiment was conducted from 2010 to 2014 to study the effects of six stocking rates on CO2 flux, and the results showed that there were significant differences in CO2 fluxes by year, treatment, and month. The effects of light and intermediate grazing remained relatively constant with grazing year, whereas the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…The MTE‐GM simulation showed that GM is beneficial for alleviating carbon release, especially for temperature grassland ecosystems (Table ). Our result is consistent with the findings of a controlled experiment from Yan et al (), which showed that light and intermediate grazing decreased ecosystem CO 2 emissions rates in the Hulunber meadow steppe of China. Meanwhile, a study of European grasslands has reported that changes in management intensity (mainly changing from intensively managed grasslands to extensively managed ones) caused a decline in net ecosystem production (Chang et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The MTE‐GM simulation showed that GM is beneficial for alleviating carbon release, especially for temperature grassland ecosystems (Table ). Our result is consistent with the findings of a controlled experiment from Yan et al (), which showed that light and intermediate grazing decreased ecosystem CO 2 emissions rates in the Hulunber meadow steppe of China. Meanwhile, a study of European grasslands has reported that changes in management intensity (mainly changing from intensively managed grasslands to extensively managed ones) caused a decline in net ecosystem production (Chang et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The metabolic footprints are the combination of carbon used for reproduction and respiration of soil nematodes. Yan et al (2017) found that CO 2 ux signi cantly decreased with increasing grazing intensity. Our results are in agreement and indicate that intensive grazing reduces the metabolic activity of soil nematodes.…”
Section: Effect Of Grazing Intensity On Carbon Utilization Of Soil Nematodesmentioning
confidence: 94%
“…A major mechanism lies in the fact that trampling by cattle in this study increased the bulk density but decreased the total soil porosity under varying degrees of grazing intensity (e.g. Ludvíková et al 2014), leading to corresponding decreases in soil respiration and decomposition of dead roots (Yan et al 2017).…”
Section: Effects Of Grazing Intensity On Carbon Transfers To Below-grmentioning
confidence: 75%
“…By stark contrast, serious defoliation under heavy grazing usually increases root exudation (Hamilton and Frank 2001;Kuzyakov et al 2001), which may increase the carbon decomposed by microorganisms in the rhizosphere. A study of the same ecosystem revealed that heavy grazing may largely lead to an increase in the proportion of root respiration relative to total soil respiration (Yan et al 2017). These results may collectively explain the significantly lowered retention of 13 C transferred from the canopy to the roots under heavy grazing.…”
Section: Effects Of Grazing Intensity On Carbon Transfers To Below-grmentioning
confidence: 95%